Bitcoin as Tool for Financial Inclusion in El Salvador: The Perils of Authoritarian Governance - Titus Meijering; Antulio Rosales (Journal of Politics in Latin America)
In 2021, El Salvador declared bitcoin legal tender. According to President Nayib Bukele, the measure was intended to expand access to financial services in a country with a high proportion of unbanked people and to cheapen and ease remittance flows for migrants and their families. In this article, we inquire about the use of bitcoin as a tool for financial inclusion and contend that this policy needs to be seen in the broader context of democratic backsliding. We show that bitcoin has not translated into financial inclusion, but instead, the bitcoin law serves as a public relations tool to capture new support from like-minded constituencies, build closer relations with them, and empower international “crypto-bros.” On the other hand, this is a tool to benefit a close circle close to the president with the use of public funds, as part of a broader historical shift of elites in El Salvador.